Investment Decision Analysis of Ritail Government Securities - Indhira Ridho Abdhilla; Vivi Armadhani; Siti Lailatus Saidah; Maria Yovita R Pandin (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to analyze the characteristics, identify and evaluate risk factors in retail SBN bonds ORI023 and ORI024 series in influencing the achievement of individual investment goals. this research method is qualitative and data collection techniques, data analysis techniques regarding the research conducted. The data collection techniques used in this research are documentation and literature studies sourced from relevant secondary data to be studied, namely in the form of stock market price data on the official yahoo finance web, scientific journals, and so on. The findings of this study indicate that the market value of ORI023 in the secondary market is Rp.998,289 and the initial market value of ORI024 is Rp. 1,000,000 which is the same as its nominal price.